The impact of human papillomavirus type on colposcopy performance in women offered HPV immunisation in a catch‐up vaccine programme: a two‐centre observational study. (9th March 2017) - Munro, A; Gillespie, C; Cotton, S; Busby‐Earle, C; Kavanagh, K; Cuschieri, K; Cubie, H; Robertson, C; Smart, L; Pollock, K; Moore, C; Palmer, T; et al.
Abstract : Objective: To determine whether human papillomavirus (HPV) immunisation has affected the prevalence of HPV genotypes and colposcopic features of cervical intraepithelial neoplasia (CIN) in young women referred for colposcopy. Design: A two‐centre observational study including vaccinated and unvaccinated women. Setting: Colposcopy clinics serving two health regions in Scotland, UK. Population: A total of 361 women aged 20–25 years attending colposcopy following an abnormal cervical cytology result at routine cervical screening. Methods: Cervical samples were obtained from women for HPV DNA genotyping and mRNA E6/E7 expression of HPV 16, 18, 31, 33, and 45. Demographic data, cytology, and histology results and colposcopic features were recorded. Chi‐square analysis was conducted to identify associations between vaccine status, HPV genotypes, and colposcopic features. Main outcome measures: Colposcopic features, HPV genotypes, mRNA expression, and cervical histology. Results: The prevalence of HPV 16 was significantly lower in the vaccinated group (8.6%) compared with the unvaccinated group (46.7%) ( P = 0.001). The number of cases of CIN2+ was significantly lower in women who had been vaccinated ( P = 0.006). The HPV vaccine did not have a statistically significant effect on commonly recognised colposcopic features, but there was a slight reduction in the positive predictive value (PPV) of colposcopy for CIN2+, from 74% (unvaccinated) to 66.7% (vaccinated). Conclusions: In this group of young women with abnormal cytology referred to colposcopy, HPV vaccination via a catch‐up programme reduced the prevalence of CIN2+ and HPV 16 infection. The reduced PPV of colposcopy for the detection of CIN2+ in women who have been vaccinated is at the lower acceptable level of the UK national cervical screening programme guidelines. Tweetable abstract: Reduction of hrHPV positivity and CIN in immunised women consistent with lower PPV of colposcopy for CIN2+. Tweetable abstract: Reduction of hrHPV positivity and CIN in immunised women consistent with lower PPV of colposcopy for CIN2+.